Inflation targeting, exchange rate and output gap in Central and Eastern European countries - Shevchuk, Victor; Kopych, Roman (Publishing House of Wroclaw University of Economics and Business, 2024)
This paper aims at empirical assessment of monetary policy relationships in Central and Eastern European countries (Czechia, Hungary, Poland, Romania), which practise the monetary regime of inflation targeting. Using quarterly data for the period of 2004-2019, the authors examined the relationship between the output gap, nominal and real exchange rate misalignment, consumer price inflation and the central bank policy rate, using the panel vector autoregression (PVAR) model. According to estimates, the central banks of the CEE-4 countries react with an increase of their policy rate to the output gap and inflation, as implied by the Taylor rule. At the same time, a monetary reaction to nominal (real) exchange rate misalignment is lost in the estimates for the post-crisis period of 2010-2019. An increase of the central bank rates does not seem to have unfavourable output effects, while the nominal exchange rate is likely to depreciate with three to five quarter lags. However, there is evidence of the price puzzle when monetary tightening is followed by a counterintuitive increase in the inflation rate. In full accordance with the New Keynesian framework, inflation depends on the output gap, while being expansionary in the real sector. Evidence of the exchange rate pass-through (ERPT) to inflation is mixed. This article provides insights into the average monetary policy reaction function and its macroeconomic effects in the CEE-4 countries, with the value added in that following the Taylor rule does not guarantee effectiveness in tackling inflation in the presence of the price puzzle. Based on the estimated exchange rate effects on the output gap and inflation, deliberate currency appreciation resulting from the central bank foreign exchange interventions and/or fiscal austerity measures can be helpful for such a disinflation that minimises output losses.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 188-206
Keywords: inflation targeting; output gap; consumer price inflation; exchange rate; Central and Eastern European (CEE) countries